Personalized Mobile Tool AskPCOS Delivering Evidence-Based Quality Information about Polycystic Ovary Syndrome - Xie, Jue; Burstein, Frada; Garad, Rhonda; Teede, Helena J.; Boyle, Jacqueline A. (Seminars in Reproductive Medicine, 2018)
Despite polycystic ovary syndrome (PCOS) being the most common endocrine condition affecting reproductive-aged women, studies have shown the information needs of PCOS consumers are not currently met. The expressed need by women with PCOS for accessible, evidence-based personalized PCOS information informed the design and development of the PCOS mobile tool—AskPCOS. The App provides a range of unique features such as: evidence-based PCOS health information, self-diagnostic function, a question prompt list to optimize health practitioner engagement, and a commonly asked questions list. A five-phase App development process involved extensive stakeholder consultation, system architecture design, development of the content repository, system prototyping, and evaluation. AskPCOS is the first evidence-based, consumer-driven mobile App developed by women and for women with PCOS and utilizes innovative technology to empower PCOS consumers and optimize health outcomes. The App content repository is enhanced by the best available evidence and expertise extracted from the International Evidence-Based Guideline in PCOS (2018). The AskPCOS App has extensive data capture capability through the usage of data gathering functions and backend analytics to optimize responsiveness to consumer needs. In addition, the multilingual content and not-for-profit cost model is designed to facilitate worldwide adoption of the tool, and address PCOS information inequities in developing countries.
Keywords: polycystic ovary syndrome; evidence-based resources; mHealth; mobile; application; health literacy; health equity